EVALUASI PERENCANAAN PENJUALAN MELALUI ANALISIS BIAYA VOLUME LABA DAN PERBANDINGANNYA DENGAN PENGAMATAN HISTORIS PENJUALAN PADA PT. BAJA UTAMA WIRASTA INTI GROUP INDONESIA, MEDAN - HILMAN LUBIS (JURNAL ILMIAH SIMANTEK, 2020)
The Data needed for this study came from a document research object that included the company's history, organizationalstructure and task description, sales budget data, fixed cost budget, variable cost budget, and 2015 profit budget, and salesrealization data, Fixed cost realization, variable cost realization, and the profit covered were 2013, 2014, and 2015 data. Thedata collection is used in the literature and field study techniques that include observation, interviews, and documentation.The type of research used is descriptive. From the results of the analysis, obtained that sales planning through historicalobservation of sales can not provide an abstract/picture of the amount of sales planning that is more precise and realistic tobe achieved so that the current in the company is planning a sale that the company does too large so that the company isnot able to implement well. Sales planning through historical observations of sales cannot provide a sales planning thatsupports the achievement of the company's profit target. It can be known by considerable deviation between the target profitand the realization of the profit that the company can achieve. Total sales of the entire product in the year 2015 is Rp.85,401,123,100 or 566,688 units, while to reach the profit target of Rp. 87,418,617,700, the company needs to seek sales ofRp. 88,682,845,517 or 590,459 units.